Synthesis of Novel 2,3-Dihydro-2,3-furandione and 1H-Pyrazole-3-Carboxylic Acid Derivatives - Hakan Ungoren, Sevket; Deniz, Bayram; Altural, Behzat (Asian Journal of Chemistry, 2016)
The reaction of oxalyl chloride with unsymmetrically substituted diketones (1a-e) furnished the corresponding 2,3-dihydro-2,3-furandiones (2a-e). In addition, 1H-phrazole-3-carboxylic acids (5c-e) were synthesized by the reaction of (2c-e) with phenylhydrazine and 1,5-diphenylcarbazide.